CTCF directly binds G-quadruplex structures to regulate genome topology and gene expression - Daniela Samaniego-Castruita; Isabella Han; Roxroy C. Morgan; Samantha Carpenter; Bryce Williams; Abhijit Chakraborty; Ishwar Radhakrishnan; Ferhat Ay; Samuel A. Myers; Anjana Rao; Vipul Shukla (Proceedings of the National Academy of Sciences, 2026)
DNA G-quadruplexes (G4s) are non-B-form secondary DNA structures that are prevalent at key regulatory regions in mammalian genome and are highly conserved across evolution. However, the mechanisms by which G4s contribute to distinct facets of genome function are not well understood. Here, we conduct a proteomics screen with G4s of diverse topologies to uncover G4 binding activities in genomic regulators of nucleosome remodeling, paraspeckle assembly, RNA splicing, and three-dimensional genome organization. Among the prominent hits, we identify the genomic architectural protein, CCCTC-binding factor (CTCF), as one of the strongest G4 binders. Building on this finding, we perform extensive biochemical validation of CTCF–G4 interaction and identify a CTCF mutant, with pronounced affinity for G4s over its consensus double-stranded DNA motif. By implementing well-established approaches and developing additional G4 mapping tools, we define a comprehensive catalog of genomic G4s and demonstrate their close association with CTCF binding. Using genetic reconstitution of mouse embryonic stem cells with a G4-specific CTCF mutant, we define the role of G4s in regulating CTCF occupancy, chromatin looping, and gene expression. Our studies reveal that G4-linked chromatin loops are stronger, persistent, and less sensitive to CTCF depletion. Collectively, our work establishes the G4 binding activity of CTCF and provides key insights into the functional significance of G4 structures.